Managing global engineering networks part I: Theoretical foundations and the unique nature of engineering. (February 2014) - Zhang, Yufeng; Gregory, Mike; Shi, Yongjiang
Network concepts have been widely reported in the current literature on international engineering operations. However, a systematic view of the unique nature of engineering is missing, and its implications for the design and operations of global engineering networks are poorly understood. This article has been written to address the above-mentioned knowledge gaps by understanding how global leading companies effectively cope with the unique nature of engineering in their network operations. A theory-building approach based on the case study methods was adopted considering the contemporary nature of this study and the complexity of the research object. The first part of this article establishes a theoretical foundation for global engineering networks through discussing the intrinsic requirements of engineering operations, understanding the influence of the external business environments, and reviewing the relevant engineering network theories and practices. A preliminary framework was developed to bring together the key issues and suggest focusing areas of investigation in the case studies.